2021
DOI: 10.1177/10820132211050847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cold plasma-assisted shrimp processing chain on biochemical and sensory quality alterations in Pacific white shrimps (Penaeus vannamei)

Abstract: In this paper, remodeling the shrimp processing chain and the effects of the transformation on the biochemical and sensory qualities of fresh Pacific white shrimp ( Penaeus vannamei) under refrigeration storage were investigated. In the proposed model, a dielectric barrier discharge atmospheric cold plasma pretreatment step using a 60 kV source for 60, 90, 120, and 150 s was introduced after the first and second wash followed by refrigeration storage at 4 ± 1 °C for 12 days. Chemical, biochemical, and sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recently, Elliot et al [ 115 ] suggested to incorporate CAP in the traditional processing chain of fresh shrimp ( Penaeus vannamei ), i.e., immediately after the traditional double wash preceding refrigerated storage at 4 °C for 12 days—a minimal treatment with cold plasma (DBD, 60 kV, 69/90/120 or 150 s). This treatment results in more desirable quality outcomes.…”
Section: Effects Of Cap Treatment Of Aquatic Foods Of Animal Origin: ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Elliot et al [ 115 ] suggested to incorporate CAP in the traditional processing chain of fresh shrimp ( Penaeus vannamei ), i.e., immediately after the traditional double wash preceding refrigerated storage at 4 °C for 12 days—a minimal treatment with cold plasma (DBD, 60 kV, 69/90/120 or 150 s). This treatment results in more desirable quality outcomes.…”
Section: Effects Of Cap Treatment Of Aquatic Foods Of Animal Origin: ...mentioning
confidence: 99%
“…The latter are characterised by low malondialdehyde concentration, low volatile nitrogen products content and comparable proximate composition as compared with the traditional approach without CAP. Texture, pH and colour are remarkably retained at 120 and 150 s of CAP pre-treatment and protein degradation is negligible up to 90 s, as opposed to 120 and 150 s of pre-treatment [ 115 ].…”
Section: Effects Of Cap Treatment Of Aquatic Foods Of Animal Origin: ...mentioning
confidence: 99%